The effect of oil price fluctuations on the Malaysian and Indonesian stock markets - Abdul Hadi, Abdul Razak; Yahya, Mohamed Hisham; Shaari, Abu Hassan (Faculty of Business and Accountancy, University of Malaya, 2009)
This study is pursued with the objective of examining the effect of changes in crude oil price on the share prices of public listed companies on Bursa Malaysia and the Jakarta Stock Exchange as proxied by the Kuala Lumpur Composite Index (KLCI) and Jakarta Composite Index (JCI), respectively. The study employs the Engle-Granger Cointegration test and Error Correction Modelling (ECM). Using time series data from January 1986 through December 2006, this study finds a significant long-term relationship between the movement of crude oil price and the performance of the two stock markets. The two observed variables in both stock markets are also found to be positively correlated. The test results from Impulse Response Function and Variance Decomposition show the presence of a dynamic interaction between the movement in crude oil prices and the two stock market indices.